Humor Seksis Pada Mahasiswa Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sumatera Utara Angkatan 2019-2020 Menurut Perspektif Komunikasi Islam - Putri Amelia; Hasnun Jauhari Ritonga; Tengku Walisyah (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
This journal discusses Sexist Humor in Students of the Faculty of Da'wah and Communication at the State Islamic University of North Sumatra Class of 2019-2020 According to an Islamic Communication Perspective, the purpose of this research is to find out the forms of sexist humor that exist in the Faculty of Da'wah and Communication of UINSU Class of 2019- 2020 and to find out the perspective of Islamic communication on sexist humor. This type of research method is a field with qualitative data analysis using descriptive research methods aiming to obtain an in-depth description of the data. Data obtained through interviews, observation, and documentation. In this study, the informants were students from the Faculty of Da'wah and Communication from the study program Islamic Communication and Broadcasting, Da'wah Management, Islamic Counseling Guidance, and Islamic Community Development. The results of this study provide answers to the problems that have been formulated, as follows: the forms of sexist humor that are accepted are body shaming in the form of joking alluding to physical problems such as body shape that looks fat and thin, tall and short, regarding skin color, and regarding appearance face. Meanwhile, apart from body shaming, bullying also comes from the accepted form of sexist humor, in the form of bullying men who have body gestures like women's, this is done when hanging out with friends. When receiving this action, many of the recipients decided to be silent and did not respond more for fear of spoiling the atmosphere and ignoring the action because they did not want to fight. However, the rate of occurrence of sexist humor at the 2019-2020 UINSU Faculty of Da'wah and Communication is still low because many people realize that this action is a bad act. In the perspective of Islamic communication towards sexist humor, of course this action is very inconsistent with Islamic communication.